Penerapan Teori Nirmana pada Komposisi Shibori Style Future Glam Sport pada Penerapan Ready to Wear - Qotrunada Salsabil Putri; Djuniwarti Djuniwarti; Mira Marlianti (Jurusan Seni Rupa ISBI Bandung, 2025)
Nirmana is a basic theory in design, and is a science of visual design. Nirmana has a huge influence on a design. Nirmana theory can be applied to Ready To Wear (RTW) designs with applications that produce novelty both in terms of appearance and composition. Shibori is a tie dye technique that is made by tying and/or covering certain parts of the fabric with thread before dyeing. The motif in the form of circular spots is inspired by meteors. The application of Shibori by applying nirmana theory makes RTW unique. The creation method used refers to Gustami, namely the stages: Exploration, Design, Realization. The final result was six RTW looks which were divided into two introducing look designs, three statement look designs, and one signature look design and the entire look was displayed in a fashion show at the JFP (Jogja Fashion Parade) event.